2011
DOI: 10.1007/s13142-011-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Is reduction in pain catastrophizing a therapeutic mechanism specific to cognitive-behavioral therapy for chronic pain?

Abstract: Mechanisms underlying favorable outcomes of psychosocial interventions for chronic pain are unclear. Theory suggests changes in maladaptive cognitions represent therapeutic mechanisms specific to cognitive-behavioral therapy (CBT). We illustrate the importance of examining whether treatments work either uniquely via mechanisms specified by theory or via mechanisms common to different treatments. Secondary data analysis was conducted to examine the effects of reduction in pain catastrophizing on outcomes follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 53 publications
4
64
0
Order By: Relevance
“…Results showed that pre- to post-treatment changes in pain catastrophizing did not differ significantly between treatments, and changes in pain catastrophizing predicted pre to post changes in outcomes comparably across them. Similar results were found for pain catastrophizing in a trial of CBT versus pain education [7]. Such results call into question whether pain catastrophizing change is a mechanism specific to CBT, but also suggest that pain catastrophizing change is an important but pervasive mechanism elicited by different treatments, even those not using deliberate cognitive change techniques.…”
supporting
confidence: 68%
“…Results showed that pre- to post-treatment changes in pain catastrophizing did not differ significantly between treatments, and changes in pain catastrophizing predicted pre to post changes in outcomes comparably across them. Similar results were found for pain catastrophizing in a trial of CBT versus pain education [7]. Such results call into question whether pain catastrophizing change is a mechanism specific to CBT, but also suggest that pain catastrophizing change is an important but pervasive mechanism elicited by different treatments, even those not using deliberate cognitive change techniques.…”
supporting
confidence: 68%
“…233 Multiple studies that employ cross-lagged panel analyses, or similar statistical approaches, have shown that substantial portions of the variability in end-of-treatment outcomes for CBT and multidisciplinary treatment can be accounted for by early-treatment changes in catastrophizing. 29;31;33 Interestingly, as recent reviews point out 102;221 , we know relatively little about the mechanisms underlying CBT and other non-pharmacologic pain treatment approaches, and it may be that disparate treatments operate in part via common mechanisms. For example, changes in catastrophizing statistically mediate the benefits of CBT 31;33;105;233 , and multidisciplinary treatment programs 50 , as well as exercise- and activity-based physical therapy interventions that do not explicitly target catastrophizing.…”
Section: Psychosocial Factors Influencing Pain-related Outcomesmentioning
confidence: 99%
“…Overall, greater catastrophizing is associated with amplified attentional focus on pain (16–18), serves as a risk factor for long-term pain (19), and correlates with the presence of disproportionately-negative sequelae of pain (e.g., worsening physical and psychological disability and/or higher healthcare costs) (20–22). Process analyses of CBT treatment studies indicate that changes in catastrophizing and negative affect precede changes in clinical pain, and that CBT’s effects on catastrophizing last for months or years (23, 24). Despite a recent proliferation of research on CBT for chronic pain, however, there has been very limited investigation of its effects on the central nervous system’s processing of pain-related information in FM (25).…”
Section: Introductionmentioning
confidence: 99%